Effect of exercise on key pharmacokinetic parameters related to metformin absorption in healthy humans: A pilot study. (5th February 2020) - Nikolaidis, Stefanos; Virgiliou, Christina; Vekiou, Magdalini; Skari, Ariadni; Kechagidou, Anna; Gika, Helen; Theodoridis, Georgios; Pappas, Periklis; Leondaritis, George; Mougios, Vassilis
Abstract : Exercise is widely accepted as having therapeutic effects; thus, it is important to know whether it interacts with medications. The aim of the present pilot study was to examine the effect of high‐intensity interval exercise (known to have antidiabetic action) on key pharmacokinetic parameters related to absorption of metformin (the first‐line medication against type 2 diabetes). Ten healthy men participated in two sessions, spaced one to two weeks apart in random, counterbalanced order. In both sessions, participants received 1000 mg of metformin orally, 1‐1.5 hours after breakfast. Then, they either ran for 60 minutes at alternating intensity, starting at 40 minutes after metformin administration, and rested without food consumption over the next 3 hours or they rested without food consumption during the entire testing period. Venous blood samples were collected before and at 0.5, 2, 2.5, 3, 3.5, 4, and 4.5 hours after metformin administration for metformin determination by liquid chromatography‐mass spectrometry. Capillary blood samples were also collected for lactate and glucose measurements. Data from the two sessions were compared through Wilcoxon or Student's t test, as appropriate. Maximum plasma concentration of metformin ( C max ) was higher at exercise compared to rest ( P = .059). Time to reach C max ( T max ) decreased with exercise ( P = .009), and the area under the metformin concentration vs time curve was higher at exercise ( P = .047). The addition of exercise to metformin administration did not cause hypoglycemia or lactic acidosis. In conclusion, our results provide the first evidence that pharmacokinetic values related to metformin absorption are affected by exercise.